2021
DOI: 10.1158/1535-7163.mct-20-0620
|View full text |Cite
|
Sign up to set email alerts
|

T Cell–Mediated Antitumor Immunity Cooperatively Induced By TGFβR1 Antagonism and Gemcitabine Counteracts Reformation of the Stromal Barrier in Pancreatic Cancer

Abstract: for their contributions and generous support for the single cell RNA sequencing work of the KPC tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Several preclinical models of solid tumour, including PDAC, demonstrated that halofuginone inhibits collagen synthesis by inhibiting TGF-β signalling [ 80 ]. By reprograming T-regs and stimulating CD8 + T cell-mediated anti-tumour activity, TGF-β inhibition in conjunction with gemcitabine effectively inhibited tumour development [ 81 ]. Of late, it has been revealed that CAFs provide TGF-β to induce tumour progression and chemoresistance by upregulating ATF4 expression [ 82 ].…”
Section: Functions Of Cafsmentioning
confidence: 99%
“…Several preclinical models of solid tumour, including PDAC, demonstrated that halofuginone inhibits collagen synthesis by inhibiting TGF-β signalling [ 80 ]. By reprograming T-regs and stimulating CD8 + T cell-mediated anti-tumour activity, TGF-β inhibition in conjunction with gemcitabine effectively inhibited tumour development [ 81 ]. Of late, it has been revealed that CAFs provide TGF-β to induce tumour progression and chemoresistance by upregulating ATF4 expression [ 82 ].…”
Section: Functions Of Cafsmentioning
confidence: 99%
“…Additionally, inhibiting TGF-β caused a reduction of Treg-mediated suppression of CD8 + T cells. This suggests that TGF-β could promote the development of effector memory Tregs with suppressive activity against CTL, further highlighting the role of TGF-β in indirectly impairing CTL function in cancer ( 30 ). To conclude, CAFs could potentially mediate induction of Tregs and suppress memory T cells, however, current evidence is not conclusive.…”
Section: Do Cafs Truly Drive Regulatory T Cell Differentiation?mentioning
confidence: 94%
“…Additionally CAFs upregulate SPRY1 in T cells associated with reduced activation and downregulate CD107, and cause a reduction in secretion of Granzyme B and TNF-α. Opposing studies report an increase or decrease of IFN-γ secretion by T cells ( 7 , 30 32 ). (F) CAFs upregulate exhaustion markers PD1, Lag3, TIGIT, Tim3and CD39 on T cells ( via e.g.…”
Section: How Do Cafs Restrict T Cell Migration?mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several chemotherapeutic agents, such as cisplatin, oxaliplatin, doxorubicin, and paclitaxel, can also enhance the expression of immune checkpoints, mostly PD-L1 (Ng et al, 2018). In this context, the expression of PD-L1 on cancer cells can associate with the PD-1 receptor on effector T cells, reducing anti-tumor immune responses and facilitating immune escape (Li et al, 2021).…”
Section: Chemotherapy Combined With Pd-l1/pd-1 Inhibitorsmentioning
confidence: 99%